A duplex RT-PCR assay for detection of H9 subtype avian influenza viruses and infectious bronchitis viruses - WEI, Yan-di (J Integr Agric, 2016)
H9 subtype avian influenza virus (AIV) and infectious bronchitis virus (IBV) are major pathogens circulating in poultry and have resulted in great economic losses due to respiratory disease and reduced egg production. As similar symptoms are elicited by the two pathogens, it is difficult for their differential diagnosis. So far, no reverse transcription-polymerase chain reaction (RT-PCR) assay has been found to differentiate between H9 AIV and IBV in one reaction. Therefore, developing a sensitive and specific method is of importance to simultaneously detect and differentiate H9 AIV and IBV. In this study, a duplex RT-PCR (dRT-PCR) was established. Two primer sets target the hemagglutinin (HA) gene of H9 AIV and the nucleocapsid (N) gene of IBV, respectively. Specific PCR products were obtained from all tested H9 AIVs and IBVs belonging to the major clades circulating in China, but not from AIVs of other subtypes or other infectious avian viruses. The sensitivity of the dRT-PCR assay corresponding to H9 AIV, IBV and mixture of H9 AIV and IBV were at a concentration of 1×10(1), 1.5×10(1) and 1.5×10(1) 50% egg infective doses (EID(50)) mL(−1), respectively. The concordance rates between the dRT-PCR and virus isolation were 99.1 and 98.2%, respectively, for detection of samples from H9N2 AIV or IBV infected chickens, while the concordance rate was 99.1% for detection of samples from H9N2 AIV and IBV co-infected chickens. Thus, the dRT-PCR assay reported herein is specific and sensitive, and suitable for the differential diagnosis of clinical infections and surveillance of H9 AIVs and IBVs.